1995
DOI: 10.1165/ajrcmb.13.4.7546779
|View full text |Cite
|
Sign up to set email alerts
|

Early cytokine production in pulmonary Cryptococcus neoformans infections distinguishes susceptible and resistant mice.

Abstract: A murine pulmonary infection model utilizing intratracheal inoculation of Cryptococcus neoformans was used to analyze cytokines produced in response to opportunistic pathogens acquired via the respiratory tract. The specific question asked was whether early cytokine secretion in lung-associated lymph nodes (LALN) would predict whether this organism would be cleared from the lung. Lung colony-forming units (CFU) were analyzed in two strains of mice over 12 wk, and lung clearance was found to be strain dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 31 publications
8
94
0
Order By: Relevance
“…Classically, defects in cellular immunity, particularly those that require T lymphocytes, are considered as the main risk factor for the mycosis, both in humans and mice (3,4). In the present study, it was observed that the susceptible mouse strain produced the highest amount of crossreactive antibodies.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Classically, defects in cellular immunity, particularly those that require T lymphocytes, are considered as the main risk factor for the mycosis, both in humans and mice (3,4). In the present study, it was observed that the susceptible mouse strain produced the highest amount of crossreactive antibodies.…”
Section: Discussionsupporting
confidence: 51%
“…C. neoformans has a polysaccharide capsule composed of glucuronoxylomannan (GXM), which acts as a major virulence factor (2) and is considered to be a thymus independent type-2 antigen (TI-2). A murine model in which C. neoformans is inoculated via intratracheal route has allowed the definition of different levels of susceptibility among the various mouse strains (3,4). It has been proposed that these differences are attributed mainly to the presence of a Th1 cellular immune response (3).…”
mentioning
confidence: 99%
“…Previous experiments in mice have highlighted the importance of Th polarization with regard to susceptibility to infection, with enhanced susceptibility to infection linked to Th2 polarization (33). Interestingly, Th2 polarization has not been associated with enhanced susceptibility to cryptococcal infection in rats (34).…”
Section: Discussionmentioning
confidence: 99%
“…This result was unexpected since mAb IgG3 has consistently been ineffective in mediating protection in various murine models of cryptococcal infection (11,12). However, the results can be understood if one considers three separate previous observations: 1) that susceptibility to C. neoformans infection varies depending on the genetic background of the host (31, 32); 2) that resistance to C. neoformans is a function of the type of immune response (33,34); and 3) that Ab efficacy is dependent on cell-mediated immunity (9, 15).…”
Section: Discussionmentioning
confidence: 99%